Organization of the Expert-Methodological Work, As a Way of Solving Problems in the System of Corporate Governance of Subsidiaries and Dependent Organizations - A. A. Usachev; M. V. Samosudov (Управление)
The article presents the experience of solving the problem of support of the system of corporate governance of subsidiaries and dependent organizations with the necessary information as well as training of specialists for the control system of the group of companies “Delicate moving”. Article is an invitation for discussion and interaction.